2012
DOI: 10.3382/ps.2012-02169
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive soundness is higher in chickens selected for low as compared with high antibody response

Abstract: White Leghorn chickens were selected for 36 generations for high (HAS) or low (LAS) antibody response to SRBC 5 d after an intravenous challenge. The aim of this study was to investigate possible changes in reproductive soundness resulting from that selection. Age and BW at onset of lay (first egg), along with weight of the first egg, were recorded on 45 hens from each line. Intensity of lay was measured as the number of ovulations within a 15-d period over 15 sequential intervals (total 225 d). Three cycles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
4
7
0
Order By: Relevance
“…Mean hatchability ranged from 65% (farm group 2) to 76% (farm group 7) while egg production ranged from 21-24 predicted eggs/hen/cycle. These hatchability values compare well with results from other authors investigating this characteristic among indigenous chicken (Albrecht, 2011;Abiola et al, 2008;Asuquo, et al, 1992). The farm group 7 with the lowest flock size trends had production values close to those of other groups.…”
Section: Journal Of Agricultural Studiessupporting
confidence: 81%
“…Mean hatchability ranged from 65% (farm group 2) to 76% (farm group 7) while egg production ranged from 21-24 predicted eggs/hen/cycle. These hatchability values compare well with results from other authors investigating this characteristic among indigenous chicken (Albrecht, 2011;Abiola et al, 2008;Asuquo, et al, 1992). The farm group 7 with the lowest flock size trends had production values close to those of other groups.…”
Section: Journal Of Agricultural Studiessupporting
confidence: 81%
“…This was also observed in a different selection experiment for SRBC antibody response: the high SRBC antibody response line laid their eggs later than the low response line (Albrecht et al, 2012b;Zhao et al, 2012). In addition, the low antibody response line showed to have a longer duration of fertility than the high antibody response line (Albrecht et al, 2012b). Martin et al (1990) found a realized genetic correlation between age at sexual maturity and antibody response to SRBC of -0.28 in a line selected for low antibody response.…”
supporting
confidence: 52%
“…Contradictory, previous studies described that hens selected for a high primary antibody response to SRBC after 29 generations laid their first egg 23 d later than hens selected for low primary specific antibody response to SRBC (Parmentier et al, 2012). This was also observed in a different selection experiment for SRBC antibody response: the high SRBC antibody response line laid their eggs later than the low response line (Albrecht et al, 2012b;Zhao et al, 2012). In addition, the low antibody response line showed to have a longer duration of fertility than the high antibody response line (Albrecht et al, 2012b).…”
mentioning
confidence: 67%
“…Data on the regularities of the weight and shell thickness changes in eggs from L + and L  published by A. Martin et al [60] and H. Albrecht et al [64] are contradictory. Probably, the reasons are the unequal duration of selection (22 and 36 generations respectively) and the differences between the genotypes of initial populations.…”
Section: Features Of Embryogenesis In Meat Hens Genotypes With Differmentioning
confidence: 99%
“…Egg laying in L  was proved to start 11.67±3.53 days earlier and layers had a lower body weight (169.46±40.20 g) than in L + as a result of selection in 36 generations of White Leghorn hens for antibody response [63,64]. At this, egg parameters were significantly greater in L + (shape index by 4.12±0.55 %, egg white height by 0.27±0.12 mm and egg white quality in Haugh units by 1.89±0.91 %).…”
Section: Features Of Embryogenesis In Meat Hens Genotypes With Differmentioning
confidence: 99%